Methionyl-tRNA Synthetase from Phaseolus aureus: Purification and Properties - Burnell, James N. (1981)
l-Methionyl-tRNA synthetase (EC 6.1.1.10) from seeds of Phaseolus aureus has been purified approximately 290-fold. Optimum assay conditions were determined by using the ATP-pyrophosphate exchange assay and the aminoacylation assay. The enzyme catalyzes both selenomethionine- and selenoethionine-dependent ATP-pyrophosphate exchange in addition to catalyzing the formation of selenomethionyl-tRNA at a rate comparable to the rate of formation of methionyl-tRNA. Competition experiments were conducted to investigate further the substrate specificity of the purified enzyme. Two peaks of methionyl-tRNA synthetase were detected by using Sephadex G-200 gel filtration; the molecular weights of the two enzymes as determined by Sephadex G-200 column chromatography were 340,000 and 85,000. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis suggests that the enzyme is a tetramer consisting of four identical monomers with molecular weights of 85,000.